Analysis of School Facilities and Infrastructure Standards to Support Learning Activities in Vocational High Schools - Rolly Robert Oroh; Israel Yonatan Fredrik Kamu; Maikel Wolter Kuhu; Arther Valentino Mananggel (Cita konsultindo, 2024)
Vocational high schools (VHS) aim to produce graduates who are ready to compete in the world of work, so supporting facilities such as study rooms and practical equipment are very important. The aim of the research is to analyze the suitability of standards for educational facilities and infrastructure in vocational high schools. The research method used is descriptive. This research took place at a vocational school in Tomohon City, North Sulawesi, Indonesia, as a case study in this research. Data collection was carried out through location observations and analysis of secondary data from schools. The research results show that the availability of facilities and infrastructure in vocational schools does not fully meet educational standards. Several facilities and infrastructure in vocational schools need to be equipped, such as laboratories, curriculum development rooms and practice rooms. Vocational schools need to collaborate with the industrial world so that formal agreements can then be built as a collaborative effort to provide facilities and infrastructure for learning and as a form of support for industrial internship practice programs for students. This research can be important for all education stakeholders in the process of determining policies related to educational standard regulations in vocational high schools.